Responsive evaluation of stakeholder dialogue as a worksite health promotion intervention to contribute to the reduction of SEP related health inequalities: a study protocol - Hanneke van Heijster; Jantien van Berkel; Tineke Abma; Cécile R. L. Boot; Emely de Vet (BMC, 2020)
Abstract Background Large health inequalities exist in the Netherlands among individuals with a high compared to a low socioeconomic position. Worksite health promotion interventions are considered promising to reduce these inequalities, however, current interventions seem not to have the desired effects. This study proposes 'moral case deliberation', a form of stakeholder dialogue on moral dilemmas, as an integrated and inclusive intervention for worksite health promotion. This intervention takes into account three factors that are considered possible underlying causes of low effectiveness of current interventions, namely the lack of deliberate attention to: 1) the diverging values and interests of stakeholders in worksite health promotion, 2) the ethical issues of worksite health promotion, and 3) the connection with the lived experience (lifeworld) of lower SEP employees. Moral case deliberation will help to gain insight in the conflicting values in worksite health promotion, which contributes to the development of a vision for worksite health promotion that is supported by all parties. Methods The intervention will be evaluated through Responsive Evaluation, a form of participatory research. Key to Responsive Evaluation is that stakeholders are consulted to determine relevant changes as a result of the intervention. The intervention will be evaluated yearly at both fixed moments (baseline and annual evaluation(s)) and continuously. Mixed methods will be used, including interviews, participatory observations, analyses of HRM-data and short questionnaires. In addition, the intervention will be evaluated economically, on both monetary and non-monetary outcomes. Discussion This protocol proposes an innovative intervention and a novel participatory evaluation in the context of worksite health promotion. The study aims to gain understanding in how dialogue on moral dilemmas on health and health promotion can contribute to heightened personal and mutual understanding among stakeholders and practice improvements in the work context. By evaluating the intervention in more than one setting, findings of this study will provide knowledge about how MCD can be adapted to specific work settings and what changes it may lead to in these settings. Trial registration Netherlands Trial Register (NRT): NL8051. Registration date: 28/09/2019, retrospectively registered. https://www.trialregister.nl/